Application of the multi-stage centrifugal compressor 1D loss model in the adiabatic compressed air energy storage. (1st May 2023) - Ma, Linrui; Zhang, Xuelin; Zhang, Zhao; Wang, Yazhou; Si, Yang; Chen, Xiaotao; Zhang, Tong; Xue, Xiaodai
Highlights: A detailed loss model of the compressor is introduced to the energy storage system. A computational efficiency design method for the compressor is proposed. The stage distribution and geometric dimensioning of the compressor can be optimized. Performance maps of the compressor under different regulations methods are analyzed. The flexibility of the system to cope with renewable energy has been confirmed. Abstract: A compressor is the core equipment used to convert and store energy in an adiabatic compressed air energy storage system. However, existing compressor models cannot be used for design and detailed loss analyses, which in turn makes simulations of the energy storage process inadequate. In response to this problem, a 1D loss model was developed and applied to an adiabatic compressed air energy storage system to realize compressor design and simulate the compression process. In the design section, based on the 1D loss model and novel optimization algorithms for the stage distribution and single-stage compressor design, we achieved detailed geometric dimensioning of every single-stage compressor and analyzed the energy loss distribution in each representative single-stage compressor. In the simulation session, we generated performance maps of the single-stage and multi-stage compressors under both speed and variable inlet guide vane regulations. Furthermore, the performance maps were combined with heat exchanger and air storage tank models to simulate the entire energy-storage process. The results show that through variable inlet guide vane regulation, the adiabatic compressed air energy storage system has good flexibility to meet different demands under fluctuating renewable energy flows.